Transforming Human Resource Practices in the Digital Age: A Study on Workforce Resilience and Innovation - Sandy Setiawan; Umi Rusilowati; Aswadi Jaya; Hetilaniar; Rion Wang (CORISINTA, 2025)
The rapid advancement of digital technologies has significantly transformed human resource (HR) practices, influencing workforce resilience and organizational innovation. As organizations navigate evolving work environments, the integration of technology-driven HR strategies has become essential for maintaining competitiveness. Traditional HR models are being replaced by more automated and data-driven systems, shaping the future of workforce management. This study aims to examine the intersection of HR practices and digital transformation, with a particular focus on how digital tools enhance workforce resilience and foster organizational innovation. It explores the role of AI-driven talent management systems, data-driven decision-making, and adaptive HR strategies in optimizing recruitment, performance evaluation, and employee engagement. A mixed-method approach was employed, combining qualitative and quantitative analyses. Data was collected through a systematic literature review, multiple case studies, and in-depth interviews with HR professionals across various industries. These methods provided comprehensive insights into the evolving landscape of digital HR practices. The findings highlight the critical role of continuous learning, agile work structures, and active employee engagement in fostering a resilient workforce. The adoption of AI-powered HR tools has proven effective in improving decision-making, employee retention, and performance management, ultimately leading to greater organizational adaptability and innovation. This study concludes that digital transformation in HR is not merely an operational shift but a strategic necessity. By successfully integrating digital tools, businesses can create a more flexible, agile, and responsive work environment, fostering long-term growth and sustainability in an increasingly competitive market.